2008
DOI: 10.1152/ajplung.00109.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide synthase/arginase balance in bronchial reactivity in patients with chronic obstructive pulmonary disease

Abstract: Competition between nitric oxide synthases (NOSs) and arginases for their common substrate l-arginine could be involved in the regulation of cholinergic airway reactivity and subsequent airway remodeling. The aims of this study were to evaluate the relationships between the expression of this enzymatic balance and the effects of NOS and arginase inhibition on bronchoconstrictive response to acetylcholine of patients without and with early chronic obstructive pulmonary disease (COPD). Twenty-two human bronchi [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…A recent pulmonary perspective supported by the National Heart, Lung, and Blood Institute stated that there is a need for methods linking in vitro observations to in vivo disease state with regard to airway smooth muscle function [12]. Along this line we show an inverse relationship between the level of resting tone and FEV 1 , which is consistent with the fact that increased smooth muscle tone may contribute to airflow limitation in COPD, as previously suggested [5,13,14]. In our limited series of patients, airflow limitation was similar whether or not endothelial dysfunction was present.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…A recent pulmonary perspective supported by the National Heart, Lung, and Blood Institute stated that there is a need for methods linking in vitro observations to in vivo disease state with regard to airway smooth muscle function [12]. Along this line we show an inverse relationship between the level of resting tone and FEV 1 , which is consistent with the fact that increased smooth muscle tone may contribute to airflow limitation in COPD, as previously suggested [5,13,14]. In our limited series of patients, airflow limitation was similar whether or not endothelial dysfunction was present.…”
Section: Introductionsupporting
confidence: 90%
“…Arterial rings were evaluated immediately after dissection, whereas bronchial rings were placed in oxygenated Krebs's solution and stored overnight at 4°C, as previously described [5,7,8].…”
Section: Pharmacological Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, our study is the first to have demonstrated the role of increased arginase activity in tobacco associatedpulmonary endothelial dysfunction. Increased arginase activity has also been associated with airway hyperresponsiveness [33,34]; we previously demonstrated that increased arginase activity is involved in airway sensitivity in smokers [35]. Overall, elevated arginase activity may be one of the mechanisms underlying both pulmonary arterial dysfunction and bronchial dysfunction [36].…”
Section: Discussionmentioning
confidence: 92%